Peer support for parents of disabled children part 1: perceived outcomes of a one‐to‐one service, a qualitative study. (17th December 2014) - Shilling, V.; Bailey, S.; Logan, S.; Morris, C.
Abstract Background Parents of disabled children are encouraged to seek peer support. Delivering one‐to‐one support requires resources; therefore, investigating how these services may impact on families and those providing the service is important when evaluating such services. Methods We carried out a qualitative study involving semi‐structured interviews and focus groups. Participants were 12 parents and 23 befrienders who had contact with the Face2Face one‐to‐one befriending service in Devon and Cornwall during a 12‐month period, and 10 professionals from health, social care and education services. Findings Shared experience was perceived central to successful peer support and was a catalyst for other elements of support, enabling parents to (i) learn from the experience of others; (ii) speak freely in a safe and non‐judgemental environment; and (iii) receive support and encouragement from their befriender. These elements underpinned perceived outcomes for both parents providing and receiving support. Outcomes for parents receiving support centred on emotional stability, personal growth and reduced isolation. Supporting parents experienced positive outcomes through their training, mutual support and the feeling that they were helping others. Parents and befrienders appeared to benefit through expanding their social network. Nevertheless providing support was reported to create emotional burden and concerns for befrienders around their performance, and also required a substantial time commitment. Conclusions Befrienders as well as parents perceived positive outcomes from their involvement in peer support although there is also potential for less positive impact on those offering support.